Answer:
The value of
.
Explanation:
Given:
![(x+3)/(x)-(x+1)/(x+4)=(5)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/qfzj2r7qnng1cdiacumzo79n1vvm0i09k8.png)
We need to solve this equation.
Solution:
First combining equation having same denominators we get;
![(x+3)/(x)-(5)/(x)=(x+1)/(x+4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/g3ptf8qt1rk86ukth8u9akivpvpzwt1idh.png)
Now denominators are common so we will solve the numerators we get;
![(x+3-5)/(x)=(x+1)/(x+4)\\\\(x-2)/(x)=(x+1)/(x+4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/1j8qx0xn9qbp2cms55mnlpe9ogi6488z3a.png)
Now by cross multiplication we get;
![(x-2)(x+4)=x(x+1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/qew8xakyi11jw4pxsi1nwabflpt5smq0gy.png)
Now Applying distributive property we get;
![x^2+4x-2x-8=x^2+x\\\\x^2+2x-8=x^2+x](https://img.qammunity.org/2021/formulas/mathematics/high-school/tjoo49s6rmnhmhgiwn21yla98bdgmhuvfp.png)
Now Combining the like terms we get;
![x^2+2x-x^2-x=8\\\\x=8](https://img.qammunity.org/2021/formulas/mathematics/high-school/n0k8wpkti8miir25jv03gn0rki6ukbxob2.png)
Hence on solving we get the value of
.